Тайна нечистой силы: повесть / Фиона Келли - Келли Фиона (Детский детектив "Чёрный котёнок", 2001)
Экземпляры: ф. 4 (20100128) / Инвентарный номер: 95783 / Цена: 32.00 / Авт.знак: К 34 / ГРНТИ: 17.82 / ББК: 84(4Вел)